"My Two Homes"Children's Picture Books and Non/Normative Imaginaries of Home in Post-Divorce/Separation Families. (2nd September 2017) - Walsh, Katie
Abstract: In spite of a burgeoning interest in children's home lives, we know little about the meaning and experience of home for children living in post-divorce/separation families who often spend time in more than one parental home. As a starting point, in this article I analyze the way in which thirteen "therapeutic" pictures books for younger children aged 3–8 represent home for such children (and their parents) through their text and images. I argue that the books contain four dominant tropes of domestic transition through their representation of the disruption, journeys, thresholds, and materialities of home. However, at the same time, the books also present the ordinariness of domestic home life in post-divorce/separation family life with a counter-narrative of the mundane time spent being together and gender-neutral parental care practices at home.